Brief High Oxygen Concentration Induces Oxidative Stress in Leukocytes and Platelets: A Randomized Cross-over Pilot Study in Healthy Male Volunteers. Issue 3 (September 2021) - Hafner, Christina; Pramhas, Sibylle; Schaubmayr, Wolfgang; Assinger, Alice; Gleiss, Andreas; Tretter, Eva Verena; Klein, Klaus Ulrich; Scharbert, Gisela
ABSTRACT: Background: Supplemental oxygen is administered routinely in the clinical setting to relieve or prevent tissue hypoxia, but excessive exposure may induce oxidative damage or disrupt essential homeostatic functions. It is speculated that oxidative stress in leukocytes and platelets may contribute to vascular diseases by promoting inflammation and cell aggregation. Methods: In this pilot study 30 healthy male volunteers (18–65 years) were exposed to high oxygen concentration (non-rebreather mask, 8 L/min, 100% O2 ) and synthetic air (non-rebreather mask, 8 L/min, 21% O2 ) in a cross-over design for 20 min at a 3-week interval. Venous blood samples were obtained at baseline and 1, 3, and 6 h postintervention. Primary outcome was generation of reactive oxygen species in leukocytes as measured by the redox-sensitive fluorescent dye dihydrorhodamine 123. Additional outcomes were oxidative stress in platelets and platelet aggregation as measured by thromboelastography (ROTEM) and Multiplate analyses. Findings: High oxygen exposure induced oxidative stress in leukocytes as evidenced by significantly higher mean fluorescence intensity (MFI) compared with synthetic air at 3 h postintervention (47% higher, P  = 0.015) and 6 h postintervention (37% higher, P  = 0.133). Oxidative stress was also detectable in platelets (33% higher MFI in comparison with synthetic air at 6 h, P  = 0.024; MFI 20% above baseline at 3 h, P   =  0.036; 37% above baseline at 6 h, P  = 0.002). ROTEM analyses demonstrated reduced mean clotting time 1 h postintervention compared with baseline (−4%, P  = 0.049), whereas there were no significant effects on other surrogate coagulation parameters. Conclusion: Clinically relevant oxygen exposure induces oxidative stress in leukocytes and platelets, which may influence the immune and clotting functions of these cells. Abstract : Supplemental Digital Content is available in the text